Digitization, Measurement and the Unmeasurable - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2017)
Research in the field of “Digital Economics” has widely neglected the dynamics of changes in preference and demand due to the exploding quantification of human life. This paper examines reactions to the rapidly expanding digital measurement of individual and societal factors. The reactions “Government Regulation”, “Flooding”, “Passive Escape: Digital Detox” and “Active Escape” are analyzed.
Keywords: O30; 330; digital economics; quantification of life; the unmeasurable; government regulation; Digital Detox; offline; nature